Fragility reduction of offshore wind turbines using tuned liquid column dampers. Issue 125 (October 2019) - Hemmati, Arash; Oterkus, Erkan; Barltrop, Nigel
Abstract: High flexibility of offshore wind turbines (OWTs) makes them vulnerable to excessive vibrations. This paper studies vibration control of offshore wind turbines induced by multi-hazard excitations. A model consisting of entire offshore wind turbine foundation and tower controlled by tuned liquid column dampers (TLCD) considering nonlinear soil pile interaction is established. The model is subjected to wave, wind, and seismic loading. The effect of severity of earthquake on the performance of the structural control device is investigated. A fragility analysis based on acceleration capacity thresholds is performed to estimate reliability improvement using the structural control devices. The fitted fragility functions based on multiple stripes analysis are constructed and compared with the empirical cumulative distribution curves. The results suggest that the use of an optimal TLCD with a mass ratio of 2.5% reduces the fragility of the system by as much as 6% and 12% for operational and parked conditions, respectively. Highlights: Optimal TLCDs reduce the standard deviation of deflections of the top of tower up to 49%. TLCDs show a better performance in mitigating undesired vibrations caused by low-intensity earthquakes. The fragility values decrease with the inclusion of the tuned liquid column damper. The maximum fragility reduction is observed for medium and high sensitive equipment up to 13%.